2018
DOI: 10.33225/jbse/18.17.765
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Polya Problem-Solving and Target-Task Collaborative Learning Approaches in Electricity Amongst High School Physics Students

Abstract: This research reports on the effectiveness of Polya Problem-Solving and Target-Task collaborative learning approaches in electricity amongst high school physics students. It also includes a gender focus. It was an experimental research with a pre-test post-test control group design. The experimental groups were exposed to Polya Problem-Solving approach and Target-Task collaborative learning approach while the control group were exposed to conventional teaching. A total of 180 students were selected an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 36 publications
0
5
0
1
Order By: Relevance
“…The positive effects of Extended Problem-Solving Strategy implementation can be supported by relevant studies in the literature, which revealed the positive effects of the use of any problem-solving strategy in physics and science education at different levels about (Bolton & Ross, 1997;Çalışkan et al, 2007;Dhillon, 1998;Dufresne, Gerace, Hardiman, & Touger, 1993;Dufrense et al, 1997;Docktor et al, 2015;Gök, 2014, Heller & Reif, 1984Hollingworth & McLoughlin, 2001;Lawson, 1978;Larkin & Reif, 1979;Lucangeli, Galderisi, & Cornoldi, 1995;Olaniyan, & Govender, 2018;Selçuk et al, 2008;Wright & Williams, 1986).…”
Section: Resultsmentioning
confidence: 83%
“…The positive effects of Extended Problem-Solving Strategy implementation can be supported by relevant studies in the literature, which revealed the positive effects of the use of any problem-solving strategy in physics and science education at different levels about (Bolton & Ross, 1997;Çalışkan et al, 2007;Dhillon, 1998;Dufresne, Gerace, Hardiman, & Touger, 1993;Dufrense et al, 1997;Docktor et al, 2015;Gök, 2014, Heller & Reif, 1984Hollingworth & McLoughlin, 2001;Lawson, 1978;Larkin & Reif, 1979;Lucangeli, Galderisi, & Cornoldi, 1995;Olaniyan, & Govender, 2018;Selçuk et al, 2008;Wright & Williams, 1986).…”
Section: Resultsmentioning
confidence: 83%
“…Critical thinking is the main capital to be a problem solver (Olaniyan & Govender, 2018). To produce students who can become problem solvers, a strong understanding of concepts is needed (Utomo & Narulita, 2018).…”
Section: Critical Thinking Of Students In Urban and Rural Schoolsmentioning
confidence: 99%
“…Students must understand the concepts to improve critical thinking [22]. If students have critical thinking skills, students can look at the situation from all sides, able to think ideally [23]. Critical thinking is the main capital to be a problem solver [24].…”
Section: " I Try To Understand By Looking At My Father When Measuring Rice Fields " " Yes I Try To Apply To Flow Through My Rice Field Rementioning
confidence: 99%